1984
DOI: 10.1139/f84-118
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Relationships between Bacterial Abundance and Chlorophyll Concentration in Fresh and Marine Waters

Abstract: A strong, positive empirical relationship was found between bacterial abundance and chlorophyll concentration in fresh and marine waters. Freshwater and marine linear regression equations are statistically indistinguishable. The overall equation is log AODC = 5.867 + 0.776 log chl a, r2 = 0.88, where AODC (acridine orange direct count) is the number of bacteria per millilitre and chl a is micrograms of chlorophyll a per litre. It is apparent that planktonic bacteria and algae are tightly linked in lakes and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
244
7
7

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(289 citation statements)
references
References 48 publications
31
244
7
7
Order By: Relevance
“…Both statistical and experimental studies indicate that P plays an important role in regulating bacterioplankton growth. These results, along with statistical evidence (Bird and Kalff 1984;Shortreed and Stockner 1986;Currie 1990), P cell content data (Vadstein et al 1988;Jiirgens and Glide 1990), and experimental evidence from other sources (e.g. Jones 1977;Toolan et al 199 l), suggest that P may be important in regulating bacterioplankton biomass or activity in a variety of aquatic systems.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Both statistical and experimental studies indicate that P plays an important role in regulating bacterioplankton growth. These results, along with statistical evidence (Bird and Kalff 1984;Shortreed and Stockner 1986;Currie 1990), P cell content data (Vadstein et al 1988;Jiirgens and Glide 1990), and experimental evidence from other sources (e.g. Jones 1977;Toolan et al 199 l), suggest that P may be important in regulating bacterioplankton biomass or activity in a variety of aquatic systems.…”
Section: Resultsmentioning
confidence: 79%
“…In addition, statistical evidence suggests that P may play an important role in determining differences in standing stocks of bacterioplankton across a wide variety of lakes (Bird and Kalff 1984;Shortreed and Stockner 1986;Currie 1990). However, because primary production is often stimulated by P (Schindler 1978), P may influence bacterioplankton indirectly by stimulating the rate at which C substrate is produced.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have shown that bacterial abundance changes with the trophic state in freshwater and marine systems (Azam et al, 1983;Fuhrman et al, 1980;Bird & Kalft, 1984;Cho & Azam, 1990;Gasol & Vaque, 1993;Pace & Cole, 1994). Within these systems, the trophic relationships are undoubtedly very.…”
Section: Introductionmentioning
confidence: 99%
“…This role may be even more important in oligotrophic systems where the biomass of the microheterotrophs often equals or exceeds that of autotrophs (Bird and Kalff 1984;Cole et al 1988;Fuhrman et al 1989;Cho and Azam 1990;Simon et al 1992;Gasol et al 1997). As a result, the dynamics of the community of microplankton is imprinted in the optical properties of seawater (Spinrad et al 1989;Stramski et al 1992).…”
Section: Wv (Nm)mentioning
confidence: 99%